A Mathematical Model of the Covid-19 Cases in Indonesia (Under and Without Lockdown Enforcement) - Sugiyanto Sugiyanto; Muchammad Abrori (Biology, Medicine, & Natural Product Chemistry, 2020)
COVID-19 stands for Corona (CO), Virus (VI), Disease (D) and year 2019 (19), which is COVID-19 first appeared in 2019. Mathematical model of covid deployment in Indonesia under and without lockdown case uses the SIRV model, such as Susceptible, Infected, Recovery, and Virus. The results of this model state that under lockdown the spread of COVID-19 could be stopped. If it were not under lockdown it can multiply 1,276 times higher over two months.